Taking offense: religion, art, and visual culture in plural configurations - Meyer, Birgit; Kruse, Christiane; Korte, Anne-Marie (dynamis, 2018)
What makes an image offensive? — This question is addressed in this volume. It explores tensions and debates about offensive images and performative practices in various settings in and beyond Europe. Its basic premise is that a deeper understanding of what is at stake in these tensions and debates calls for a multidisciplinary conversation. The authors focus on images that appear to trigger strongly negative reactions; images that are perceived as insulting or offensive; those subject to taboos and restrictions; or those that are condemned as blasphemous. In light of recurrent acts of violence leveled against images and symbols in the contemporary, globally entangled world, addressing instances of “icono-clash” (Bruno Latour) from a new post-secular, global perspective has become a matter of urgency.